GE_GERICHTE P/13360/2012 vom 2. Mai 2013 - GE Cour de justice (2013)
MENDICITÉ; DROIT FONDAMENTAL; DISPOSITIONS PÉNALES DE LA LCR | CPP.263; CPP.398.4; CEDH.10; CEDH.8; LPG.11A; Cst.8.2; Cst.36.3; LCR.90.1; LCR.49; LCI.14; RPSS.1.1; OCR.46.2; CP.21; CP.70.1